'Hard, primitive and below the belt': The Korean War, Prisoners of War, and Training for Conduct After Capture. (April 2021) - Fitzpatrick, Meghan
This article looks at what impact the Korean War (1950–53) had on British policy regarding how soldiers should behave if captured by the enemy. It explores the training available to the average serviceman between the First World War and the early 1950s and examines how fears of brainwashing prompted the first major investigation of prisoner behaviour and training in modern British history. Using primary sources, the article also traces how the war contributed to a philosophical shift in attitudes towards the prisoner of war and a reassessment of the skills necessary to survive on the modern battlefield.